The Xanthomonas citri Reverse Fitness Deficiency by Activating a Novel β-Glucosidase Under Low Osmostress - Li, Kaihuai; Liao, Jinxing; Wei, Ming; Qiu, Shanxu; Wu, Weiyin; Zhao, Yancun; Wang, Haihong; Liu, Qiongguang; Liu, Fengquan; Chang, Changqing (Frontiers in microbiology, 2022)
Bacteria can withstand various types of environmental osmostress. A sudden rise in osmostress affects bacterial cell growth that is countered by activating special genes. The change of osmostress is generally a slow process under the natural environment. However, the collective response of bacteria to low osmostress remains unknown. This study revealed that the deletion of phoP (Δ phoP ) from X. citri significantly compromised the growth and virulence as compared to the wild-type strain. Interestingly, low osmostress reversed physiological deficiencies of X. citri phoP mutant related to bacterial growth and virulence. The results also provided biochemical and genetic evidence that the physiological deficiency of phoP mutant can be reversed by low osmostress induced β-glucosidase (BglS) expression. Based on the data, this study proposes a novel regulatory mechanism of a novel β-glucosidase activation in X. citri through low osmostress to reverse the fitness deficiency.